Using Collagen Peptides From the Skin of Monkfish (Lophius litulon) to Ameliorate Kidney Damage in High-Fat Diet Fed Mice by Regulating the Nrf2 Pathway and NLRP3 Signaling - Miao, Bingtao; Zheng, Jiawen; Zheng, Guoping; Tian, Xiaoxiao; Zhang, Wen; Yuan, Falei; Yang, Zuisu (Frontiers in Nutrition, 2022)
Background Oxidative stress and inflammation play important roles in high-fat diet (HFD) induced kidney damage. Previous studies show that the collagen extracted from the skin of monkfish (Lophius litulon) with pepsin (pepsin-solubilized collagen, PSC) exhibits good biological activities. This study investigates the protective effect of PSCP against chronic kidney injury in HFD-fed mice. Methods Pepsin-solubilized collagen was further hydrolyzed into collagen peptides, and the compound with the best 2,2-diphenyl-1-picrylhydrazyl (DPPH) clearance rate was named pepsin-solubilized collagen peptide (PSCP). A group of mice were fed an HFD for 4 weeks, and then for another 6 weeks PSCP was added to their diet at the amount of either 100 or 200 mg/kg. Results Pepsin-solubilized collagen peptide treatment (200 mg/kg) reduced the mice's serum levels of uric acid (UA), creatinine (CRE), and blood urea nitrogen (BUN) by 27, 20, and 37%, respectively. This treatment also remarkably improved renal histopathology. Moreover, the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) were increased by 96, 52, and 74%, respectively, and decreased the malondialdehyde (MDA) level by 36%. Additionally, PSCP activated the Nrf2 pathway and inhibited NLRP3 signaling to significantly reduce the levels of inflammatory cytokines IL-1β, IL-6, and TNF-α. Conclusions Our results indicate that compound PSCP has the potential to prevent or control chronic kidney damage.